A review of child stunting determinants in Indonesia. Issue 4 (17th May 2018) - Beal, Ty; Tumilowicz, Alison; Sutrisna, Aang; Izwardy, Doddy; Neufeld, Lynnette M.
Abstract: Child stunting reduction is the first of 6 goals in the Global Nutrition Targets for 2025 and a key indicator in the second Sustainable Development Goal of Zero Hunger. The prevalence of child stunting in Indonesia has remained high over the past decade, and at the national level is approximately 37%. It is unclear whether current approaches to reduce child stunting align with the scientific evidence in Indonesia. We use the World Health Organization conceptual framework on child stunting to review the available literature and identify what has been studied and can be concluded about the determinants of child stunting in Indonesia and where data gaps remain. Consistent evidence suggests nonexclusive breastfeeding for the first 6 months, low household socio‐economic status, premature birth, short birth length, and low maternal height and education are particularly important child stunting determinants in Indonesia. Children from households with both unimproved latrines and untreated drinking water are also at increased risk. Community and societal factors—particularly, poor access to health care and living in rural areas—have been repeatedly associated with child stunting. Published studies are lacking on how education; society and culture; agriculture and food systems; and water, sanitation, and the environment contribute to child stunting. This comprehensive synthesis of the available evidence on child stunting determinants in Indonesia outlines who are the most vulnerable to stunting, which interventions have been most successful, and what new research is needed to fill knowledge gaps.